PENGARUH MODEL PEMBELAJARAN KOOPERATIF STAD BERBASIS MULTI MEDIA INTERAKTIF TERHADAP PENGUASAAN KONSEP SISWA PADA MATERI TERMODINAMIKA - Jamuri -; Kosim -; Aris Doyan (Jurnal Penelitian Pendidikan IPA, 2015)
The objective of  this study is : To know The influence of learning cooperative  STAD  model based on  interactive multi media toward  the student’s mastery concept of thermodynamics. Type of study  done ,is experimental research  by  pretest-post test control group design. Population study is XI grade of Science students in SMAN 5 Mataram. The sample was chosen two classes which taken 73 students  with random sampling which  consisted  of 37 students for experiment and 36 students for control. In this research taken through pretest and posttest by using the ability of problem solving  student test toward experiment class and control class.  The data  analyzed by using N- gain  to know the  increase percentage of problem solving of student’s ability in each class. And  ANAVA analysis to know cooperative learning model of  STAD type based on interactive multi media  toward the mastery of student concept  in thermodynamics. Analysis result  of N-gain  shows that value  reaches 70%    with high category in mastery of student concept in experiment class. Whereas, the mastery of student concept  in control class reaches 50% with average category. ANAVA analysis  in significant level  5% shows significant score gotten 0,000  0,05 from significant level used. Based on the result of ANAVA analysis could be concluded  that  the use of  cooperative learning  model of STAD type  based on interactive multimedia in  learning thermodynamics influence toward the student’s mastery concept, Keywords: Learning Cooperative, Interactive Multi Media learning, Mastery Concept and problem solving ability